2014
DOI: 10.3892/mco.2014.458
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor polymorphisms as effect modifiers of oral squamous cell carcinoma risk: A systematic review and meta-analysis

Abstract: Abstract.Smoking is one of the main risk factors for the development of oral squamous cell carcinoma (OSCC). Smoking may affect single-nucleotide polymorphism (SNP)-dependent vascular endothelial growth factor (VEGF)-induced angiogenic activity. Therefore, we systematically reviewed the published VEGF-SNP genotype data of OSCC patients and healthy individuals and performed a meta-analysis comparing the VEGF-SNP genotypes of smoking and non-smoking patients in association with OSCC incidence. Prospective and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Ferner scheinen Varianten im Genlocus von VEGF das individuelle Risiko für die Entstehung eines Kopf-Hals-Karzinoms signifikant zu beeinflussen [112]. Die VEGF-Expression gilt mittlerweile als unabhängiger Prognosemarker bei Kopf-Hals-Karzinomen [113][114][115].…”
Section: Vascular Endothelial Growth Factor (Vegf)unclassified
“…Ferner scheinen Varianten im Genlocus von VEGF das individuelle Risiko für die Entstehung eines Kopf-Hals-Karzinoms signifikant zu beeinflussen [112]. Die VEGF-Expression gilt mittlerweile als unabhängiger Prognosemarker bei Kopf-Hals-Karzinomen [113][114][115].…”
Section: Vascular Endothelial Growth Factor (Vegf)unclassified
“…One meta-analysis [ 94 ] found based on the study of nine primary level papers that immunohistochemical overexpression of VEGF was significantly associated with poor survival. Three meta-analyses have investigated the influence of various types of VEGF gene polymorphisms on the risk of developing oral cancer [ 76 , 92 , 93 ], only finding an increased risk associated with the 936C/T polymorphism. Finally, a systematic review without meta-analysis in head and neck carcinomas [ 69 ] found in the subgroup of studies on oral cancer (two studies) a lack of influence of FGFR overexpression on survival.…”
Section: Discussionmentioning
confidence: 99%